EFEKTIVITAS MODEL PROBLEM-BASED LEARNING BERBANTUAN MEDIA NUMERASITES TERHADAP KEMAMPUAN NUMERASI SISWA - Putri, Adella Harlifna; Ulya, Himmatul; Bintoro, Henry Suryo (Universitas Insan Budi Utomo, 2025)
The low numeracy skills of students at SMP Negeri 1 Mejobo are reflected in the results of a preliminary study on students in class VIII I, with an average score of 27.21. Based on these findings, this study aims to improve the numeracy skills of class VIII students through the application of the Problem-Based Learning (PBL) learning model assisted by Numerasites media. This study uses a quantitative approach with a quasi-experimental design, students in class VIII I are designated as the experimental group and students in class VIII F as the control group. Sampling was carried out using simple random sampling. Initial data analysis includes normality tests, homogeneity tests, and average equality tests. Final data analysis was carried out through independent two-sample t-tests and N-Gain calculations. The instrument used in this study was a numeracy ability test. The results of the study show: (1) The average numeracy skills of students who participated in PBL learning assisted by Numerasites media were superior compared to students who received conventional learning; (2) There is a significant increase in numeracy skills before and after implementing the PBL model assisted by Numerasites media, with the improvement category being high.